Case Report: Cadonilimab-related toxic epidermal necrolysis-like reactions successfully treated with supplemental Adalimumab - Chen, Peng-Yu; Li, Zi-Yun; Cai, Sui-Qing (Frontiers in Immunology, 2023)
Cadonilimab is the first bi-specific antibody approved for certain malignancies in June 2022, which has a modified Fc structure to reduce immune-related adverse events. To date, no reports have described Cadonilimab-related toxic epidermal necrolysis (TEN). Here, we report the first case of TEN-like reactions occurring during the treatment of hepatocellular carcinoma with Cadonilimab in combination with Lenvatinib and transarterial chemoembolization, successfully treated with supplemental Adalimumab. We confirmed Cadonilimab as the culprit and observed significant improvement in the patient's condition following Adalimumab treatment. The case emphasizes the potential risk of Cadonilimab inducing TEN, and suggests that supplemental Adalimumab could be a favorable option for treating refractory Cadonilimab-related TEN.